Near-infrared absorption optical filter

By adjusting the composition ratio of the near-infrared absorption filter and adding sulfur as a reducing agent, the interference problem of infrared rays with wavelengths of 940nm on imaging quality is solved, and the high absorption effect of filters with a thickness of less than 0.7mm on the near-infrared rays is achieved and The high penetration rate of visible light areas improves product stability and efficiency.

CN119200067AInactive Publication Date: 2024-12-27IRIDIUM OPTICS TECHNOLOGY NANTONG INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411697949.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art cannot effectively solve the interference of infrared rays with wavelengths of 940 nm on the imaging quality of biometric components and camera components, and there is a lack of filters with excellent absorption effects on the market.

Method used

It is made of iron containing 15 to 35% by weight, aluminum of 5 to 20% by weight, silicon of 1 to 10% by weight, 40 to 75% by weight, calcium of 0.2 to 10% by weight, magnesium of 1 ~10% by weight of zinc and 0.1 to 1% sulfur near infrared absorption filters are made by adjusting the composition ratio and adding sulfur as a reducing agent to make a filter with a thickness of less than 0.7mm, achieving light for 930 to 950nm. high absorption effect.

Benefits of technology

Under the premise of small thickness, excellent near-infrared filtering performance is achieved, product stability and yield are improved, production costs are reduced, efficiency is improved, and high penetration rate in visible light areas is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119200067A_ABST
    Figure CN119200067A_ABST
Patent Text Reader

Abstract

The present invention relates to a near-infrared absorption filter comprising 15-35% by weight of iron, 5-20% by weight of aluminum, 1-10% by weight of silicon, 40-75% by weight of phosphorus, 0.2-10% by weight of calcium, 0.2-10% by weight of magnesium, 1-10% by weight of zinc and 0.1-1% by weight of sulfur, the average transmittance of the near-infrared absorption filter to light having a wavelength of 930-950 nm being less than 15%, the thickness of the near-infrared absorption filter being less than 0.7 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an optical element, in particular to a near-infrared absorption filter. Background Art

[0002] With the advancement of technology, many products equipped with biometric components have appeared on the market. Such biometric components can recognize faces, fingerprints, irises or veins, etc. They use infrared rays with a wavelength of 940nm as light sources. However, infrared rays will affect the imaging quality of the sensing components, especially for devices with both biometric components and camera components. The closer the distance between them, the more serious the interference. Therefore, there is a demand in the market for filters with excellent absorption effects of infrared rays with a wavelength of 940nm. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a near-infrared absorption filter to overcome the deficiencies of the prior art.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is: A near-infrared absorption filter comprises 15-35% by weight of iron, 5-20% by weight of aluminum, 1-10% by weight of silicon, 40-75% by weight of phosphorus, 0.2-10% by weight of calcium, 0.2-10% by weight of magnesium, 1-10% by weight of zinc and 0.1-1% by weight of sulfur. The near-infrared absorption filter has an average transmittance of less than 15% for light with a wavelength between 930 and 950 nm, and a thickness of less than 0.7 mm.

[0005] In one embodiment, the average transmittance of the light with a wavelength between 420 nm and 650 nm is greater than 80%.

[0006] In one embodiment, it further comprises 0-10% by weight of an alkali metal.

[0007] In one embodiment, the alkali metal is one or more of lithium, sodium, and potassium.

[0008] In one embodiment, it further comprises 0-10% by weight of boron.

[0009] In one embodiment, it further comprises 0.5-5% by weight of a sulfur-free reducing agent, wherein the sulfur-free reducing agent is one or more of glucose, carbon, and metal powder.

[0010] In one embodiment, the thickness is between 0.25 mm and 0.6 mm.

[0011] In one embodiment, the average transmittance of the light with a wavelength between 930 nm and 950 nm is less than 13%.

[0012] In one embodiment, the semi-transmitting wavelength is between 700 nm and 800 nm.

[0013] In one embodiment, the semi-transmitting wavelength is between 715 nm and 785 nm.

[0014] In one embodiment, it contains one or more of elemental sulfur, sodium sulfide, and iron sulfide.

[0015] In one embodiment, the transmittance of light with a wavelength of 940 nm is less than 12%.

[0016] In one embodiment, the transmittance of light with a wavelength of 650 nm is greater than 82%.

[0017] In one embodiment, the thickness is less than 0.3 mm.

[0018] In one embodiment, the semi-transmitting wavelength is between 760 and 785 nm. In summary, the near-infrared absorption filter of the present invention has excellent near-infrared filtering performance with a small thickness by setting its component ratio, and the inclusion of sulfur components can improve the stability of the product, increase the yield, reduce production costs, and improve efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] To further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the following detailed description and drawings are only used to illustrate the present invention, and are not intended to limit the scope of protection of the present invention.

[0020] Figure 1 The transmittance spectra of the near-infrared absorption filters prepared in Comparative Examples 1 to 5 for light with a wavelength of 350 to 1100 nm; Figure 2 The transmittance spectra of the near-infrared absorption filters prepared in Comparative Examples 6 to 10 for light with a wavelength of 350 to 1100 nm; Figure 3 The transmittance spectra of the near-infrared absorption filters prepared in Examples 1 to 5 for light with a wavelength of 350 to 1100 nm; Figure 4 is the transmittance spectrum of the near infrared absorption filter of Examples 6 to 10 for light with a wavelength of 350 to 1100 nm; Figure 5 Spectra of the transmittance of the near infrared absorption filters of Example 11 and Comparative Example 11 to light with a wavelength of 350 to 1100 nm. DETAILED DESCRIPTION

[0021] The following describes the implementation of the present invention through specific embodiments. Those skilled in the art to which the present invention belongs can understand the spirit, advantages and effects of the present invention based on the contents described in the present invention.

[0022] When the present invention “includes,” “comprising,” or “has” specific elements, unless otherwise stated, other elements, components, structures, regions, parts, devices, systems, steps, or connections may be included without excluding such other elements.

[0023] The near infrared absorption filter of the present invention comprises 15-35% by weight of iron, 5-20% by weight of aluminum, 1-10% by weight of silicon, 40-75% by weight of phosphorus, 0.2-10% by weight of calcium, 0.2-10% by weight of magnesium, 1-10% by weight of zinc and 0.1-1% by weight of sulfur. In some embodiments, the content of iron can be 15%, 20%, 25%, 30%, or 35% by weight, the content of aluminum can be 5%, 10%, 15%, or 20% by weight, and the content of silicon can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.6%, 1.8%, 1.9%, 2.10%, 2.20%, 2.30%, 2.40%, 2.50%, 2.60%, 2.70%, 2.80%, 2.90%, 2.91%, 2.92%, 2.93%, 2.94%, 2.95%, 2.96%, 2.97%, 2.98%, 2.99%, 3.03%, 3.04%, 3.05%, 3.06%, 3.07%, 3.08%, 3.09%, 3.10%, 3.09%, 3.11%, 3.12%, 3.13%, 3.14%, 3.09%, 3.08%, 3.09%, 3.09%, 3.08%, 3.09%, 3.09%, 3.08%, 3.09%, 3.09%, 3.09%, 3.09%, 3.09%, The content of phosphorus can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, or 75% by weight, and the content of calcium can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% by weight, the content of phosphorus can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, or 75% by weight, and the content of calcium can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2 %, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% by weight and the magnesium content can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% The zinc content can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% by weight, and the sulfur content can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1% by weight, but is not limited thereto.

[0024] In some embodiments, the near-infrared absorption filter of the present invention further comprises 0-10% by weight of boron. In some embodiments, the content of boron may be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% by weight, but is not limited thereto. In one embodiment, the near-infrared absorption filter of the present invention substantially does not comprise boron.

[0025] In some embodiments, the near-infrared absorption filter of the present invention further comprises 0 to 10% by weight of an alkali metal, wherein the alkali metal is one or more of lithium, sodium, and potassium. In some embodiments, the content of the alkali metal may be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10% by weight, but is not limited thereto. In one embodiment, the near-infrared absorption filter of the present invention substantially does not comprise an alkali metal.

[0026] In order to make the thickness of the filter thinner, the iron content in the filter must be increased. However, in this case, the iron content in the filter is relatively high, and a reducing agent needs to be added to help reduce the iron ions to avoid the formation of trivalent iron. Trivalent iron absorbs the visible light region near the ultraviolet region, making the glass appear brownish yellow, while divalent iron absorbs the visible light region near the near infrared region, making the glass appear blue-green. Therefore, in order to achieve the near-infrared absorption filter in the present invention, the formation of trivalent iron needs to be avoided as much as possible. As the iron content in the filter increases, the amount of reducing agent used also increases, and the proportion of each component also needs to be adjusted with the reducing agent. However, there is an upper limit to the amount of reducing agent used. Adding too much may cause the glass to crystallize. In order to achieve a sufficient reduction effect, the process may also be further adjusted, such as additionally giving a reducing gas reducing agent, such as nitrogen, argon, or hydrogen and a mixed gas thereof, to ensure that divalent iron is obtained. Moreover, when the iron content is high, the glass manufacturing process needs to be carried out at a higher temperature (for example, 1300°), and the process requirements become higher. In addition, when the iron content in the filter increases, the glass is easy to crystallize and difficult to shape, and even if a reducing agent is used, it cannot provide sufficient reducing power, resulting in a large amount of undesirable trivalent iron.

[0027] The near-infrared filter of the present invention can obtain divalent iron stably by adding sulfur as a reducing agent and adjusting the ratio of each component in the filter. Specifically, to form the near-infrared absorption filter of the present invention, metaphosphates such as aluminum metaphosphate, lithium metaphosphate, sodium metaphosphate, potassium metaphosphate, magnesium metaphosphate, zinc metaphosphate and calcium metaphosphate can be used; carbonates such as sodium carbonate, potassium carbonate, magnesium carbonate and calcium carbonate; metal oxides such as iron oxide, aluminum oxide, zinc oxide, magnesium oxide, boron oxide and silicon oxide; elemental sulfur or sulfide (such as sodium sulfide, iron sulfide, etc.) can be used.

[0028] The near-infrared absorption filter of the present invention can be made using glass raw materials using existing technology, such as putting each glass raw material into a crucible, then putting the crucible into a reducing atmosphere furnace, and controlling the temperature between 1200° and 1500°, then stirring and clarifying the molten glass, flowing out of the mold and annealing to finally obtain homogenized glass. The reducing gas in the reducing atmosphere furnace can be nitrogen, argon, or hydrogen and a mixture thereof.

[0029] The near infrared absorption filter of the present invention includes sulfur as a reducing agent. Under the premise of containing sulfur, organic substances such as glucose, carbon, metal powder, etc. can be added as reducing agents. The content of the reducing agent without sulfur is 0.5 to 5% by weight. If the added amount is less than 0.5% by weight, the reducing effect may be insufficient; if it is greater than 5% by weight, it will cause crystallization and it will be difficult to form glass. The metal powder can be tin, zinc or aluminum.

[0030] The near-infrared absorption filter in the present invention is relatively thin, less than 0.7 mm. In some embodiments, the thickness can be 0.25 mm, 0.3 mm, 0.4 mm, 0.5 mm, or 0.6 mm, but is not limited thereto. Generally speaking, the thinner the thickness of the near-infrared absorption filter, the worse its near-infrared absorption effect. Therefore, in order to achieve a better near-infrared absorption effect, the near-infrared absorption filter on the market is often made thicker. The near-infrared absorption filter in the present invention can still achieve excellent optical performance under the premise of being thin.

[0031] The near-infrared absorption filter of the present invention has excellent optical properties. Specifically, its average transmittance for light with a wavelength between 930 and 950 nm is less than 15%. In some embodiments, its average transmittance for light with a wavelength between 930 and 950 nm is 14.5%, 14%, 13.5%, 13%, 12.5%, 12%, 11.5%, 11%, 10.5%, 10%, 9.5%, 9%, 8.5%, 8%, 7.5%, 7%, 6.5%, 6%, 5.5%, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1%, or 0.5%, but is not limited thereto.

[0032] In some embodiments, the near-infrared absorption filter of the present invention has a transmittance of light of a wavelength of 940 nm that is less than 12%, such as 11.9%, 11.8%, 11.7%, 11.6%, 11.5%, 11.4%, 11.3%, 11.2%, 11.1%, 11%, 10.5%, 10%, 9.5%, 9%, 8.5%, 8%, 7.5%, 7%, 6.5%, 6%, 5.5%, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1%, or 0.5%, but is not limited thereto.

[0033] The near-infrared absorption filter of the present invention has excellent optical properties. Specifically, its semi-penetration wavelength (T50%) is at least 700nm and above, such as its semi-penetration wavelength is between 700~800nm, or its semi-penetration wavelength is between 715~785nm, or between 760~785nm. In some embodiments, its semi-penetration wavelength can be 715nm, 720nm, 725nm, 730nm, 735nm, 740nm, 745nm, 750nm, 755nm, 760nm, 765nm, 770nm, 775nm, 780nm, 785nm, but is not limited to this. Therefore, the visible light region maintains a high transmittance. The high transmittance specifically means that the average transmittance of the near-infrared absorption filter of the present invention for light with a wavelength between 420 and 650 nm is greater than 80%. In some embodiments, the average transmittance is 81%, 82.5%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, and 90%, but is not limited thereto.

[0034] Please refer to Table 1 and Table 2, Table 1 shows the ratio of the main element oxides or main elements in Comparative Examples 1 to 10 and Examples 1 to 11, expressed in mole % and weight %, and Table 2 shows the ratio of the main elements in Comparative Examples 1 to 10 and Examples 1 to 11, expressed in weight %. 100 to 300 g of raw materials of various components are weighed according to the ratios in Table 1 and Table 2, and fully mixed to obtain a raw material composition, and the raw material composition is placed in a crucible, and then the crucible is placed in a reducing atmosphere furnace, and the temperature of the reducing atmosphere furnace is controlled to be between 1200° and 1500°, and then the molten glass is stirred, clarified, flowed out of the mold and annealed to form, and finally the near-infrared absorption filters of Comparative Examples 1 to 10 and Examples 1 to 11 are obtained, wherein no reducing agent is added in Comparative Examples 1 to 5, 0.85% by weight of reducing agent tin is added in Comparative Examples 6 to 10, and 0.23% by weight of reducing agent sulfur is added in Examples 1 to 11.

[0035]

[0036]

[0037]

[0038]

[0039]

[0040]

[0041]

[0042] like Figure 1As shown in FIG. 1 , the transmittance spectra of the near infrared absorption filters of Comparative Examples 1 to 5 for light with a wavelength of 350 to 1100 nm are shown. Table 3 shows the thickness and spectrum data of the near infrared absorption filters of Comparative Examples 1 to 5. The thickness of the near infrared absorption filters is 0.25 mm. Figure 1 As shown in Table 3, the average transmittance of Comparative Examples 1 to 5 without reducing agent in the visible light region of 420-650 nm is extremely unstable, and only Comparative Example 1 reaches more than 80%, while Comparative Example 5 is only 26.31%, which is a defective filter. The average transmittance of Comparative Examples 1 to 5 in the near-infrared region of 930-950 nm is also extremely unstable, among which Comparative Examples 4 and 5 are both greater than 24%, which are defective filters.

[0043] like Figure 2 As shown, the transmittance spectra of the near infrared absorption filters of Comparative Examples 6 to 10 for light with a wavelength of 350 to 1100 nm are shown in Table 4. The thickness and spectrum data of the near infrared absorption filters of Comparative Examples 6 to 10 are all 0.25 mm. Figure 2 As shown in Table 4, the average transmittance of Comparative Examples 6 to 10 with reducing agent tin in the visible light region of wavelength 420-650nm is also unstable. Only Comparative Examples 6, 7, and 9 reach more than 80%, while Comparative Examples 8 and 10 are both less than 70%, which are defective filters.

[0044] like Figure 3 As shown in Table 4, the transmittance spectra of the near infrared absorption filters of Examples 1 to 5 for light with a wavelength of 350 to 1100 nm are shown. Table 5 shows the thickness and spectrum data of the near infrared absorption filters of Examples 1 to 5. The thickness of the near infrared absorption filters is 0.25 mm. Figure 3 As shown in Table 5, the average transmittance of Examples 1 to 5 with reducing agent sulfur in the visible light region of wavelength 420-650 nm is very stable, all reaching more than 87%, and the average transmittance of Examples 1 to 5 in the near-infrared region of wavelength 930-950 nm is also very stable, all less than 12.1%.

[0045] like Figure 4 , which are the transmittance spectra of the near infrared absorption filters of Examples 6 to 10 for light with a wavelength of 350 to 1100 nm, and Table 5 which are the thickness and spectrum data of the near infrared absorption filters of Examples 6 to 10, respectively, wherein the thicknesses are 0.25 mm, 0.3 mm, 0.4 mm, 0.5 mm, and 0.6 mm. Figure 5 As shown in Table 6, the average transmittance in the visible light region of 420-650 nm is very stable, reaching more than 84.4%, and the average transmittance in the near-infrared region of 930-950 nm in Examples 6 to 10 is also very stable, all less than 11%.

[0046] like Figure 5 As shown, the transmittance spectra of the near-infrared absorption filters of Comparative Example 11 and Example 11 for light with a wavelength of 350~1100nm are shown in Table 5. The thickness and spectral data of the near-infrared absorption filters of Comparative Example 11 and Example 11 are shown in Table 5. The thickness of Example 11 is 0.25mm, and Comparative Example 11 is a commercially available near-infrared absorption filter with a thickness of 0.7mm. The spectra of the two are relatively close, but the thickness of Comparative Example 11 is much greater than that of Example 11.

[0047] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Therefore, all equivalent technical changes made using the description and drawings of the present invention are included in the protection scope of the present invention.

Claims

1. A near-infrared absorption filter, characterized in that: It includes 15-35% by weight of iron, 5-20% by weight of aluminum, 1-10% by weight of silicon, 40-75% by weight of phosphorus, 0.2-10% by weight of calcium, 0.2-10% by weight of magnesium, 1-10% by weight of zinc and 0.1-1% by weight of sulfur. The average transmittance of the near-infrared absorption filter to light with a wavelength between 930 and 950 nm is less than 15%, and the thickness of the near-infrared absorption filter is less than 0.7 mm.

2. The near infrared absorption filter according to claim 1, characterized in that: Its average transmittance for light with a wavelength between 420 and 650 nm is greater than 80%.

3. The near infrared absorption filter according to claim 1, characterized in that: It also includes 0.5-5% by weight of a sulfur-free reducing agent, wherein the sulfur-free reducing agent is one or more of glucose, carbon, and metal powder.

4. The near infrared absorption filter according to claim 1, characterized in that: Its thickness is between 0.25~0.6mm.

5. The near infrared absorption filter according to claim 1, characterized in that: Its average transmittance for light with a wavelength between 930 and 950 nm is less than 13%.

6. The near infrared absorption filter according to claim 1, characterized in that: Its semi-penetration wavelength is between 700~800nm.

7. The near infrared absorption filter according to claim 6, characterized in that: Its semi-penetrating wavelength is between 715 and 785 nm.

8. The near infrared absorption filter according to claim 1, characterized in that: It contains one or more of elemental sulfur, sodium sulfide, and iron sulfide.

9. The near infrared absorption filter according to claim 1, characterized in that: Its transmittance to light with a wavelength of 940nm is less than 12%.

10. The near infrared absorption filter according to claim 1, characterized in that: Its transmittance to light with a wavelength of 650nm is greater than 82%.

11. The near infrared absorption filter according to claim 1, characterized in that: Its thickness is less than 0.3mm.

12. The near infrared absorption filter according to claim 11, characterized in that: Its semi-penetration wavelength is between 760~785nm.

Citation Information

Patent Citations

  • Strong near-infrared absorption polysulfide metal complex as well as preparation method and application thereof

    CN103483391A

  • Lithium containing glass with high oxidized iron content and method of making same

    CN104136386A

  • Near-infrared absorbing glass and near-infrared cut-off filter

    CN115716706A

  • Heat absorbing blue soda-lime-silica glass

    US3652303A

  • Neutral gray glass

    US3723142A